2010
DOI: 10.3892/or_00000899
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 2-[18F] fluoro-2-deoxy-D-glucose positron emission tomography in differential diagnosis of benign and malignant intraductal papillary-mucinous neoplasm of the pancreas

Abstract: Abstract. Intraductal papillary-mucinous neoplasm (IPMN) of the pancreas presents in various histopathological stages from benign to malignant lesions. The differentiation between benign and malignant IPMN is important in order t o determine the treatment of the patients. However, preoperative differentiation remains difficult. The aim of this study was to assess the utility of 2-[18 F] fluoro-2-deoxy-Dglucose positron emission tomography (FDG-PET) in preoperative differentiation of benign and malignant IPMN o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Overall, 986 records were identified. After screening the titles and abstracts according to our inclusion and exclusion criteria, 100 full-text articles were assessed for eligibility and 10 studies [15][16][17][18][19][20][21][22][23][24] were ultimately included in our critical appraisal ( Figure 1). Patients' data were collected and analyzed on the basis of their radiological or metabolic diagnostic findings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 986 records were identified. After screening the titles and abstracts according to our inclusion and exclusion criteria, 100 full-text articles were assessed for eligibility and 10 studies [15][16][17][18][19][20][21][22][23][24] were ultimately included in our critical appraisal ( Figure 1). Patients' data were collected and analyzed on the basis of their radiological or metabolic diagnostic findings.…”
Section: Resultsmentioning
confidence: 99%
“…The SUV max cut-offs used in the different studies to differentiate benign from malignant lesions ranged from 1.3 to 3.0, with a mean value of 2.3. Several authors [15,16,18,19,24] used a SUV max of 2.5 as the cut-off for malignancy on the strength of previous reports in the literature. Takanami et al [17] adopted a value of 2.3, based on a receiver operating characteristic curve (ROC) analysis in the cohort study balancing the sensitivity and specificity of different cut-offs.…”
Section: Diagnostic Accuracy Of 18-fdg Pet Scan To Identify Malignantmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1018 patients (1019 lesions) from 17 direct comparison studies using 2 or more preoperative imaging modalities were included for differentiating malignant from benign PCL or IPMN. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Of 17 studies, 4 were performed in a prospective manner. 27,30,34,35 The mean age of the patients was 63.2 years, and 43.8% (446/1019) of the lesions were found to be malignant by surgery, biopsy, or clinical follow-up.…”
Section: Baseline Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The largest study assessing the reliability 18 F-FDG-PET in this clinical scenario was by Sperti et al [31] who demonstrated in their cohort of 64 patients with suspected IPMNs that 18 F-FDG-PET had a greater sensitivity (92 versus 58 %), specificity (97 versus 82 %), and accuracy (95 versus 72 %) than conventional imaging. Another study by Tomimaru et al [32] reported on 29 patients who underwent CT, 18 F-FDG-PET, and surgery for IPMNs, followed by histopathological examination. They found that the SUVmax on 18 F-FDG-PET correlated with the histopathological types of IPMN (benign adenoma, carcinoma in situ, or invasive carcinoma).…”
Section: Diagnosismentioning
confidence: 99%